Giant hydronephrosis in radiology: Learning from incidental findings to improve diagnostic accuracy - Lokesh Rana; Varun Bansal; Pooja Gurnal; Narvir S Chauhan (Radiology Case Reports)
The giant Hydronephrosis is defined as dilated pelvic collecting system of kidney containing more than 1 liter of fluid or at least 1.6% of body weight or kidney occupying half of the abdominal cavity. The pelvic ureteric junction (PUJ) obstruction is the commonest cause and a rarely encountered entity nowadays because of availability of advanced diagnostic imaging. We herein report a case of 21-year-old female presenting with abdominal distension for past 6 months without significant pain or tenderness which on CT shows presence of right sided massive hydronephrosis and PUJ obstruction with approximately 20 liters of fluid in the collecting system. The giant Hydronephrosis a rare entity resulting from PUJ obstruction presenting commonly with distension only rarely pain is associated. Though Cross-sectional imaging confirm the diagnosis and help localizing the origin of the lesion but the massive size of lesion make it difficult to differentiate from pelvic benign cystic lesions particularly in females especially when the lesion is occupying almost entire abdominal cavity as in our case, which is rarely encountered.